Edukasi Flipbook Animasi sebagai Media Pembelajaran pada Sanggar Bimbingan - Aisyiyah Kampung Pandan Kuala Lumpur Malaysia: Educational Flipbook Animation as Learning Media at Guidance Studio - Aisyiyah Kampung Pandan Kuala Lumpur Malaysia - Sumarna, Imam Budi (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Education in today's digital era requires innovation in learning methods to make it more interesting and effective. One innovation that can be used is an animated flip book. An animated flip book is a collection of images arranged in sequence and when flipped quickly will create the illusion of movement. This media can be an interesting tool for elementary school students to understand the subject matter more easily and with fun. So it is necessary to develop animated flipbooks as educational media in elementary schools can be an innovative solution in improving the quality of learning. By involving various parties and conducting continuous evaluations, animated flip books can be optimized to meet the needs of education in the digital era at the PCIM Malaysia Learning Studio.